Influence of ball-milled low purity boron powder on the superconductivity of MgB2 - Xu, X.; Kim, J. H.; Yeoh, W. K.; Rindfleisch, A.; Tomsic, A.; dos Santos, Dayse I.; Don, S. X. (Institute of Electrical and Electronics Engineers (IEEE), 2007)
MgB2 samples were prepared using as-supplied commercial 96% boron with strong crystalline phase and the same 96% boron (B) after ball milling. The effects of the properties of the starting B powder on the superconductivity were evaluated. We observed that samples using ball-milled 96% B, in comparison with the one made from the as-supplied 96% B, were character- ized by small grain size, broadened full width at half maximum (FWHM), and enhanced magnetic critical current density (J(c)). J(c) reached 2 x 10(3) Acm(-2) at 5 K and 8 T. The improved pinning of these samples seems to be caused by enhanced grain boundary pinning at high field.
Keywords: ball milling; crystallinity; magnetic critical current density; MgB2